Spatio-Temporal Analysis of the Hepatitis B Prevalence in Irani-an Blood Donors from 2000 to 2016 at National and Provincial Level - Negar Rezaei; Mahtab Maghsodlu; Ali Sheidaei; Sedigheh Amini Kafiabad; Kimiya Gohari; Maryam Zadsar; Farnaz Delavari; Zohreh Sharifi; Moein Yoosefi; Farshad Farzadfar; Mohsen Asadi-Lari (Tehran University of Medical Sciences, 2021)
Background: High risk blood transfusions can cause a lot of financial and psychological burden to the community. The prevalence of Hepatitis B is useful for evaluating the blood products' safety and donor selection methods. We aimed to predict the prevalence of hepatitis B in Iranian blood donors from 2000-2016. Methods: Positive cases of hepatitis B from 2006 to 2014 were collected from Iranian Blood Transfusion Organization. This database was classified according to the age, provinces, and type of donation. Data was not existed in all subnational levels and all years, therefore, for predicting the hepatitis B prevalence, two separate, Spatio-temporal and mixed model (GLMM) were developed. Results: At the national level, the hepatitis B prevalence declined from 0.69 (0.51 to 0.90) in 2000 to 0.27 (0.21 to 0.33) in 2016. In first-time, regular, and repeated donors, this prevalence declined from 2.31 (1.74 to 2.31), 0.26 (0.19 to 0.34), and 0.51 (0.38 to 0.68) in 2000 to 0.87 (0.69 to 1.09), 0.09 (0.07 to 0.12), and 0.19 (0.14 to 0.24) in 2016. At the provincial level, the highest and lowest prevalence in 2016 was observed in North Khorasan and Gilan. With increasing age, the average prevalence of hepatitis B, increased. Conclusion: Prevalence of hepatitis B in Iranian blood donors has been reduced significantly over 17 years, but still new cases of hepatitis B are reported. By precise monitoring the donor selection process and implementing more sensitive laboratory screening, we can reduce the risk of new infectious agents.